Brain alpha- and beta-globin expression after intracerebral hemorrhage - He, Yangdong (2010)
Our recent study has demonstrated that hemoglobin (Hb) is present in cerebral neurons and neuronal Hb is inducible after cerebral ischemia. In the present study, we examined the effects of intracerebral hemorrhage (ICH) on the mRNA levels of the α-globin (HbA) and the β-globin (HbB) components of Hb and Hb protein in the brain in vivo and in vitro. In vivo, male Sprague-Dawley rats received either a needle insertion (sham) or an infusion of autologous whole blood into the basal ganglia and were killed at different time points. In vitro, cultured rat brain cells were used for HbA, HbB and Hb determination. Cultured neurons were exposed to 50 or 100 μM hemin for 24 h. Some neurons also were treated with deferoxamine, an iron chelator, or vehicle. Levels of HbA and HbB, Hb and hemopexin, a transporter of heme, were measured. We found that HbA, HbB and Hb are primarily expressed in neurons, with much lower expression in astrocytes and microglia. HbA, HbB and Hb expression in the perihematomal zone was increased after ICH and Hb was localized in neurons and glia. Hemin increased HbA, HbB and hemopexin mRNA levels in cultured neurons. Deferoxamine reduced hemin-induced neuronal Hb expression. ICH increased HbA and HbB expression in the brain, which may potentially serve to buffer the heme released during clot resolution.